Socioeconomic deprivation and prognostic outcomes in acute coronary syndrome: a meta-analysis using multidimensional socioeconomic status indices - Anand, Vickram Vijay (2023)
Background: Low socioeconomic status (SES) is an important prognosticator amongst patients with acute coronary syndrome (ACS). This paper analysed the effects of SES on ACS outcomes. Methods: Medline and Embase were searched for articles reporting outcomes of ACS patients stratified by SES using a multidimensional index, comprising at least 2 of the following components: Income, Education and Employment. A comparative meta-analysis was conducted using random-effects models to estimate the risk ratio of all-cause mortality in low SES vs high SES populations, stratified according to geographical region, study year, follow-up duration and SES index. Results: A total of 29 studies comprising of 301,340 individuals were included, of whom 43.7% were classified as low SES. While patients of both SES groups had similar cardiovascular risk profiles, ACS patients of low SES had significantly higher risk of all-cause mortality (adjusted HR:1.19, 95%CI: 1.10–1.1.29, p < 0.001) compared to patients of high SES, with higher 1-year mortality (RR:1.08, 95%CI:1.03–1.13, p = 0.0057) but not 30-day mortality (RR:1.07, 95%CI:0.98–1.16, p = 0.1003). Despite having similar rates of ST-elevation myocardial infarction and non-ST-elevation ACS, individuals with low SES had lower rates of coronary revascularisation (RR:0.95, 95%CI:0.91–0.99, p = 0.0115) and had higher cerebrovascular accident risk (RR:1.25, 95%CI:1.01–1.55, p = 0.0469). Excess mortality risk was independent of region (p = 0.2636), study year (p = 0.7271) and duration of follow-up (p = 0.0604) but was dependent on the SES index used (p < 0.0001). Conclusion: Low SES is associated with increased mortality post-ACS, with suboptimal coronary revascularisation rates compared to those of high SES. Concerted efforts are needed to address the global ACS-related socioeconomic inequity. Registration and protocol: The current study was registered with PROSPERO, ID: CRD42022347987.